Bioenergy for landscape restoration and livelihoods: Re-creating energy-smart ecosystems on degraded landscapes - Baral, H.; Leksono, B.; Seol, M. (Center for International Forestry Research, 2022)
Land restoration and bioenergy are leading solutions for climate change and sustainable development. But restoration is often perceived as “going back to the past” and bioenergy development is not devoid of controversies over its impacts on land use and communities. This book shows how, under the right conditions, the two objectives of land restoration and bioenergy production are not antagonistic, but synergetic. It provides evidence and lessons from six years of pioneering initiatives in Indonesia to combine these objectives in a people-centred focus. It will be very useful for a range of stakeholders in the land and energy sectors to expand a modern and ecological agenda.